Single point mutations at the S129 residue of α-synuclein and their effect on structure, aggregation, and neurotoxicity - Pandit, Esha; Das, Lopamudra; Das, Anoy Kumar; Dolui, Sandip; Saha, Saumen; Pal, Uttam; Mondal, Animesh; Chowdhury, Joydeep; Biswas, Subhas C.; Maiti, Nakul C. (Frontiers in Chemistry, 2023)
Parkinson’s disease is an age-related neurological disorder and the pathology of the disease is linked to different types of aggregates of α-synuclein (aS) which is an intrinsically disordered protein. The C-terminal domain (residues 96-140) of the protein is highly fluctuating and possesses random/disordered coil conformation. Thus the region plays a significant role in the protein's solubility and stability by interaction with other parts of the protein. In the current investigation, we examined the structure and aggregation behavior of two artificial single point mutations at a C-terminal residue at position 129 that represent a serine residue in the wild type human aS (wt aS). Compared to wt aS, the mutants S129A and S129W imparted structural stability and showed enhanced propensity towards α-helical secondary structure. Circular dichroism (CD) analysis showed proclivity of the mutant proteins towards α-helical conformation. The enhancement of α-helical propensity lengthened the lag phase of fibril formation. Growth rate of β-sheet rich fibrillation was also reduced. Cytotoxicity tests on SH-SY5Y neuronal cell lines established that the S129A and S129W mutants and their aggregates were potentially less toxic compared to wt aS. The average survivability rate was ~40% for cells treated with oligomers (presumably formed after 24 h of incubation of the freshly prepared monomeric protein solution) produced from wt aS compared to ~80% for cells treated with oligomers obtained from mutant proteins. The relative structural stability with α-helical propensity of the mutants could be a plausible reason for their slow rate of oligomerization and fibrillation and, this was also the possible reason for reduced toxicity to neuronal cells.